Ethylene vinyl acetate nanocomposites with hybrid silicate nanofillers of destabilized natural and commercial bentonites and organomontmorillonites. Issue 4 (1st April 2019) - Ahmad Fauzi, Asfa Amalia; Osman, Azlin Fazlina; Abdullah, Mohd Aidil Adhha; Mandal, Subrata; Ananthakrishan, Rajakumar
Abstract : In this research, the interlayer destabilization process of bentonite was applied to gain a loosely packed, swelled, and disorganized clay layered structure for better polymer intercalation and filler dispersion during the fabrication of ethylene vinyl acetate (EVA) nanocomposites. Three different destabilization methods were applied to natural and commercial bentonites and their effects on swelling and platelets' ordering of the clays were observed. X‐ray diffraction results suggest that the destabilization process through a combination of pH control and salt addition is more efficient in swelling both types of bentonite clays. This was supported by field emission scanning electron microscopy analysis where smaller, more loosely packed, and uniform platelets were observed due to swelling of both natural and commercial bentonite clays. The "destabilized" bentonites were used as the co‐nanofiller with the organically modified montmorillonite (OMMT) to form hybrid silicate nanofillers for EVA matrix reinforcement. Results show that the "destabilized" natural bentonite (NB) prepared by the combination of pH control and salt addition is most efficient in reinforcing the EVA matrix when combined with the OMMT by achieving 124.9% increment in tensile strength and 190.8% in toughness values. This could be related to the improved dispersion of bentonites upon the destabilization process that allows greater matrix–filler interactions in the nanocomposite system. In summary, the destabilization process through the combination of pH control and salt addition is the promising and practical technique to improve the dispersion of bentonites throughout the EVA matrix. Without the use of expensive and toxic chemicals, it can be adopted as a new approach to swell bentonites for more environmentally friendly nanocomposite technology. J. VINYL ADDIT. TECHNOL., 25:396–411, 2019. © 2019 Society of Plastics Engineers